Reliability Analysis of Different Configurations of Master and Back-Up Systems Used in Maritime Navigation - Agnieszka Blokus; Przemysław Dziula (Journal of Marine Science and Engineering, 2020)
This paper presents a comparison of the reliability of various configurations of electronic navigation appliances, from a single system not duplicated (without back-up) to complex systems built of a master system and different numbers of reserve (back-up) systems. For reliability analysis, we created a model of an electronic navigation system reflecting the influence of the number of reserve systems on the entire system reliability. Navigation systems were analyzed as multistate systems. Assuming that they degrade from the state of full reliability to entire failure, their basic reliability characteristics were determined. We also conducted a comparison of system lifetimes in certain reliability state subsets, for different system configurations depending on the number of back-up systems. Additionally, the relationship between the costs associated with setting up a system with a certain configuration and its mean lifetime in reliability state subsets is shown. We also propose procedures for determining the moment of exceeding the allowed limit of system safety, with the use of reliability functions determined for different configurations of the system. One of the major conclusions arising from the reliability analysis is that setting a navigation system with a certain number of back-up solutions is of key importance to improve the system’s reliability in the initial period of operation, while the number of back-up systems has a minor influence on the overall system lifetime.